FEMS microbiology ecology. - Federation of European Microbiological Societies (Oxford : Oxford University Press, 1985)
FEMS Microbiology Ecology publishes high quality papers that make a significant contribution to the field. It covers microorganisms in soil, aquatic and atmospheric habitats - including extreme environments - and includes natural, artificial and managed systems.
"Published on behalf of Federation of European Microbiological Societies"--Home page.
Supersedes in part (in 1985): FEMS Microbiology Letters (Netherlands) (0378-1097).
Description based on online resource; title from home page (viewed on October 3, 2016).
Keywords: Microbial ecology -- Periodicals; Microbiology -- Periodicals